The impact of consumers' sustainability consciousness on sustainable purchase intention amongst Gen Z in the South African fashion retail market - Williams, Mymoena (Accounting and Accountability in Africa, 2022)
A new generation of conscious consumers have placed pressure on fashion retail businesses to implement sustainability into their respective business operations. Conscious consumerism is a driving force behind sustainable consumption as these consumers play a strong role when influencing business practices. Although many retailers have adapted responsible procedures by offering sustainable products to their consumers, there is a lack of research on identifying and understanding the conscious consumer holistically. The aim of the present research is to gain a better understanding of the conscious consumer in relation to the three pillars of sustainability (people, planet, profit). This study sets out to examine the Generation Z consumer market as they display traits of sustainable behaviour and also aims to unpack the main drivers of their sustainable purchase intentions within the South African fashion retail market. A self-administered online questionnaire was used to collect data from respondents between the ages of 18 and 24 years. From the self-administered questionnaires, 159 responses were completed and deemed usable. Data were analysed using Statistical Package for the Social Sciences (SPSS) version 24 and Analysis of Moment Structures (AMOS) version 24. Firstly, descriptive statistics was used to provide an overview of the sample. Secondly, Structural Equation Modelling (SEM) was used to examine the relationship between the variables. This study found that the Health and Labelling and Peer Pressure dimensions of the Consumers' Sustainability Consciousness construct has a positive influence on Sustainable Purchase Intentions. In conclusion, the findings of this study have several important implications for academia, fashion retailers and government. The contribution of this study aims to enhance the existing literature on conscious consumption by showcasing the most reliable dimensions of Consumers' Sustainability Consciousness and Sustainable Purchase Intentions. The study offers significant insights for fashion retailers and government as the impact of eating healthy, the role of product labels and peer pressure were found to have a positive influence on Gen Z's intentions to purchase sustainably. Ultimately, the insights from this body of work will generate both important implications and opportunities for further research.